Preparation and characterization of antimicrobial laminated films based on poly(lactic acid)/chitosan via a lamination technique - Thawanrat Chaisit; Punnanee Sumpavapol; Kittisak Jantanasakulwong; Thorsak Kittikorn (eXPRESS Polymer Letters, 2022)
Nowadays, there has been an increase in demand for using biodegradable food packaging due to its sustainable and environmentally friendly. Poly(lactic acid) is an interesting alternative. To increase the potential use of packaging, the development of a bioactive packaging by using a natural antimicrobial like chitosan has gained considerable attention due to its excellent antimicrobial activity and performance meanwhile, both layers have different surface properties that result in poor interfacial adhesion. So, this research aims to improve the interfacial adhesion between PLA and chitosan by grafting chitosan with 3-(trimethoxysilyl)propyl methacrylate (TMSPM) using ultrasonic vibration and to study the preparation of the laminated film via lamination technique. From the FTIR results, the characteristic peaks at a wavenumber of 1701 and 877 cm–1 corresponding to the C=O vibration in the methacrylate and Si–O stretching groups of TMSPM were observed. This indicates that the grafting reaction occurs completely. Interestingly, the PLA/CS_10%TMSPM laminated film revealed an improved interfacial adhesion and hydrophobicity. This was observed from the strength value that increased from 21.9 to 35.8 MPa and the water vapor permeability value that decreased from 14.6·10–7 to 9.1·10–7 (g·m)/(m2·Pa·s) when compared to the PLA/CS laminated film. In addition, the PLA/CS_10%TMSPM laminated film also showed excellent antimicrobial activity against E. coli as well.